2021
DOI: 10.1088/1742-6596/2089/1/012017
|View full text |Cite
|
Sign up to set email alerts
|

Designing of Lithium - Ion Battery Pack Rechargeable on a Hybrid System with Battery Management System (BMS) for DC Loads of Low Power Applications – A Prototype Model

Abstract: Now a days, Li-ion batteries are quite possibly the most exceptional battery-powered batteries; these are drawing in much consideration from recent many years. M Whittingham first proposed lithium-ion battery technology in the 1970s, using titanium sulphide for the cathode and lithium metal for the anode. Li-ion batteries are the force to be reckoned with for the advanced electronic upset in this cutting-edge versatile society, solely utilized in cell phones and PC computers. A battery is a Pack of cells organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Any average person needs a light for a few hours until the regular power supply is restored [6]. It is preferable to choose different equipment to satisfy this need to deal with this urgent circumstance [7]. The importance of stationary lead-acid batteries as a reliable source of everyday power for control and instrumentation and emergency backup power is growing [8].…”
Section: Introductionmentioning
confidence: 99%
“…Any average person needs a light for a few hours until the regular power supply is restored [6]. It is preferable to choose different equipment to satisfy this need to deal with this urgent circumstance [7]. The importance of stationary lead-acid batteries as a reliable source of everyday power for control and instrumentation and emergency backup power is growing [8].…”
Section: Introductionmentioning
confidence: 99%
“…This lighting system can serve as an alternative means of illumination in any location when there is a power outage [18]. It is particularly useful in remote or rural areas where there is a lack of electricity [19], [31] [32]. It may be used for signaling, as torches, or as outdoor light source [27].…”
Section: Introductionmentioning
confidence: 99%
“…Simulation and application-based studies have been carried out in BMS related to electric bicycles [7][8][9][10]. However, due to the 88 novelty of these products, a limited number of studies were found in this area [11][12]. The features of the BMS system can be changed according to the system.…”
Section: Introductionmentioning
confidence: 99%